THE EARLY EXPOSURE OF BUSINESS DURING TEENAGE LIFE AND THE INTENTION OF BECOMING AN ENTREPRENEUR - Manissha Lai; Nur Nailah Nisrina binti Mohd Azlan; Asyherra Ainur Azwa binti Khas-Rin; Betrisia Parrow @ Robert (Malaysian Journal of Business and Economics (MJBE), 2021)
Unemployment has been a big issue for fresh graduates nowadays because of the limitation of job opportunities due to the financial crisis and health pandemics. To measure whether there is a chance for Malaysian citizens to create more job opportunities, this research paper examines the early exposure of business during teenage life and determine the intention of becoming an entrepreneur in the near future. Using the Theory of Planned Behaviour, this study aims to identify those factors of early exposure of a business in teenage life, family influences, and social trends which can influence fresh graduates in becoming an entrepreneur. We conducted a pilot test to measure the reliability and validity of the instrument using questionnaires through Google form. There are 21 questions in total and the targeted respondents are 30 people throughout Malaysia. But to come up with a more significant outcome of our research, 56 more questionnaires had been distributed with an amount of 86 respondents in total. The form was answered anonymously and only those who are in the age of 13 to 32 were considered for analysis. All the questions contained in the questionnaire passed the Cronbach’s Alpha Test for reliability. The independent variables are early exposure of a business in teenage life, family influences, and social trends while the dependent variable is the intention of becoming an entrepreneur.